STUDI PENERIMAAN DAN PREFERENSI KONSUMEN TERHADAP MINYAK GORENG CURAH YANG DIFORTIFIKASI VITAMIN A - Martianto, Drajat; Marliyati, Sri Anna; Retnaningsih, Retnaningsih; Mulyono, Handaru Tri (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2009)
Vitamin A fortification in unbranded palm oil is an alternative solution to overcome Vitamin A deficiency problem. It, however, needs further study to determine consumer acceptance and preference of the Vitamin Afortified unbranded palm oil in order to make the fortified oil is acceptable and consumed by consumer. This study was divided into two steps, they are field study, held in Barrang Lompo Island - Makassar and Babakan Village - Bogor, and laboratory study, held in Organoleptic Laboratory and Food Processing Laboratory in Department of Community Nutrition, Bogor Agricultural University. Percentage of panelist assessment and non-parametric statistical test (Kruskal- Wallis Test) was used to measure consumer acceptance and preference of fortified unbranded palm oil. The result of this study indicated that the color and aroma of fortified unbranded palm oil is accepted by the consumer. The color, aroma, and taste of food that processed with fortified unbranded palm oil were also accepted by the consumer. The complaint during the usage of fortified unbranded palm oil were mainly caused by the way consumer used and storing the sample. Thus, it can be concluded that there were no change between fortified unbranded palm oil characteristics, both used in a controlled circumstances (laboratory) and in an uncontrolled circumstances (household).